Visualization of neurotransmitter uptake and release in serotonergic neurons - Lau, Thorsten; Schloss, Patrick (Journal of neuroscience methods, 2015)
To study serotonergic volume neurotransmission at cellular level it needs to investigate neurotransmitter release and re-uptake sites in serotonergic neurons. However, due to the low number of cell bodies in the raphe nuclei and their widely branching neurites, serotonergic neuronal cultures are not accessible ex vivo. We have combined differentiation protocols for the generation of stem cell-derived serotonergic neurons together with confocal microscopy to study the uptake and release of fluorescent substrates known to be selectively taken up by monoaminergic neurons. These substances include: (i) 4-(4-(dimethylamino)styryl)-N-methylpyridiunium (ASP+), an analog of the neurotoxin MPP+; (ii) the fluorescent false neurotransmitter (FFN511); and (iii) serotonin (5-hydroxytryptamine; 5-HT) itself, which is known to emit fluorescence upon excitation at 320-460nm. ASP+ is taken up into living serotonergic neurons through the serotonin transporter, but not accumulated into synaptic vesicles; FFN511 diffuses in a SERT-independent way into serotonergic neurons and accumulated into synaptic vesicles. KCl-induced release of FFN511 and 5-HT can be visualized and quantified in living serotonergic neurons. Application of ASP+ so far has been used to investigate substrate/transporter interactions; studies on FFN511 uptake and release have only been performed in dopaminergic neurons; quantitative studies on uptake and release of 5-HT in living serotonergic neurons have not been reported yet. The differentiation protocols for the generation of stem cell-derived serotonergic neurons combined with the application of different fluorescent dyes allow to quantify neurotransmitter uptake and release in living serotonergic neurons in vitro.